1997
DOI: 10.4315/0362-028x-60.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phenothrin and Its Metabolite 3-Phenoxybenzoic Acid (PBA) in Agricultural Products by GC and Ion-Trap GC/MS

Abstract: A sensitive method for analysis of phenothrin and its metabolite 3-phenoxybenzoic acid (PBA) in agricultural products by gas chromatography with electron capture detection (ECD-GC) and ion-trap gas chromatography/mass spectrometry (GC/MS) with chemical ionization (Cl) was investigated. After phenothrin in vegetables, fruits, potatoes, starches, and tea had been extracted with acetone, or in cereals and beans had been extracted with acetonitrile followed by Florisi! column chromatography, it was reextracted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
1
Order By: Relevance
“…The values in the studies have varied from sample to sample. [12,13]. The recovery value for promecarb is slightly lower than the literature.…”
Section: Accuracycontrasting
confidence: 54%
See 1 more Smart Citation
“…The values in the studies have varied from sample to sample. [12,13]. The recovery value for promecarb is slightly lower than the literature.…”
Section: Accuracycontrasting
confidence: 54%
“…Numerous analytical methods for determining penconazole, promecarb and phenothrin residues in various matrix have been published. Analyses of pesticides have been based on chromatographic and spectroscopic methods [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Before penconazole, promecarb and phenothrin residues were determined, samples required sample preaperation part (extraction and purification) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we showed that this is due to the combination of two factors: the formation of reagent ions is energetically of low cost and the storage of reagent ions is more efficient than with other "classical" reagents. 11 Isobutane CI has been used in environmental analysis for the detection of insecticides 48,49 and pesticides. [50][51][52] It has also been widely used in medical and veterinary research as well as in analytical toxicology for the detection of propafenone (antiarrhythmic agent) 53 animal drug residues, 54 cocaine, 55 cannabidiol 56 and their metabolites.…”
Section: Isobutanementioning
confidence: 99%